Is there a link between Hepatitis A virus and Guillain-Barré syndrome? A systematic review of case reports - Amirhosein Ghasemi; Nima Broomand Lomer; Alia Saberi (eNeurologicalSci)
Introduction: Guillain-Barré syndrome (GBS) is an inflammatory disorder of the peripheral nervous system, causing acute flaccid paralysis. There have been occasional reports linking Hepatitis A virus (HAV) to GBS. Here we aimed to evaluate the current literature on the association between GBS and HAV, exploring potential mechanisms and clinical implications. Methods: We conducted a systematic search using PRISMA guidelines in PubMed, Web of Science, Embase, and Scopus. Only published case reports or conference abstracts presenting cases of confirmed HAV infection and GBS were included. Data extraction was performed independently by two reviewers, and quality assessment was conducted using the Joanna Briggs Institute critical appraisal tool. Results: Out of 581 studies identified, 46 studies encompassing 47 cases met the inclusion criteria. The mean age of patients was 29.47 years, with a male predominance (70.2 %). Geographically, most cases were reported in Asia (74.5 %). Clinical manifestations of HAV included fever, malaise, and jaundice, while GBS presented with muscle weakness and areflexia. Laboratory findings showed albuminocytological dissociation in 76.2 % of cases. Nerve conduction studies predominantly indicated AIDP subtype (32/46, 69.6 %). Treatment involved IVIG, plasmapheresis, and supportive care, with recovery times ranging from one week to 18 months. One fatality was reported. Conclusions: This review suggests a potential link between HAV infection and GBS, proposing a mechanism: molecular mimicry. It emphasizes the need for increased awareness and preventive measures, especially in areas with lower health standards. However, further research is needed to clarify the possible mechanisms and deepen our understanding.